Effectiveness of cinnamon (Cinnamomum burmannii) extract against Streptococcus mutans in children’s dental caries: Efektivitas ekstrak kayu manis (Cinnamomum burmannii) terhadap Streptococcus mutans pada karies gigi anak - Putu Yetty Nugraha; Eko Sri Yuni Astuti; Ni Putu Tania Nadyanti Tunggadewi (Makassar Dental Journal, 2021)
The main cause of dental caries is pathogenic microorganism such as Streptococcus mutans bacteria. The most practical ways to prevent dental caries are by inhibiting and killing the bacteria. The purpose of this study is to determine the cinnamon extract can inhibit the growth of S.mutans. Dilution method was used to determine the capability of the cinnamon extract in inhibiting and killing S.mutans. The extract was obtained by maceration method and the concentration were 20%, 40%, 80% and 100%. The results showed that the extract with a minimum concentration of 40% could inhibit bacterial growth while there were not found any bacteria growing on at 80% and 100% as well as using 0.2% as a positive control. Normality test using the Shapiro-Wilk method found that the value of p(sig) > 0.05, so the data are normally distributed. On homogeneity test using the Levene test, the value of p(sig) = 0.001, while the value of p (Sig) < 0.05, so the data were not homogeneous. Then it was continued by one-way Anova to determine the different between treatment groups with value of p (sig) < 0.05 was obtained which means that there is a significant difference. Tamhanes test was conducted to determine the difference on each concentration. There is a sig-nificant difference between positive and negative control as well as on 20% and 40% concentration. The minimum killing ca-pacity concentration is 80% as bacteria are still founded on 40% concentration. It can be concluded that the present of alkaloid, flavonoid, tannin, saponin, phenol, steroid and triterpenoid that contained in cinnamon extract have antibacterial properties and have the capability of inhibiting and killing S.mutans.